Rancang Bangun Mesin Uji Aus Berbasis ASTM G65 - Kurniawan, Kurniawan; Elka Institan, Yogi (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Manufaktur Bandung (Polman Bandung), 2022)
To support advanced material research, a machine that can perform wear testing is needed, one of which refers to the ASTM G65 standard. This journal contains the process of making the design of ASTM G65-based wear test equipment with the scope of design, construction, validation and verification. Validation at the design stage is carried out by vibration analysis using Ansys software. From the data obtained, transmissibility analysis was carried out so that it can be validated that the vibrations that occur in the engine are safe and do not interfere with engine performance. Next, the prototype construction of the ASTM G65 engine was carried out and continued with validation and calibration to conform to the ASTM G65 specifications. Then a wear test is carried out on a material to find out that the machine is working according to the test scheme. Verification of the test results is carried out by comparing the test results with the tests that have been carried out on other scientific studies to ensure authentic test results.